Estabilidade, congruência e flexibilidade na tutela coletiva - Destefenni, Marcos (2008)
The present study focuses on the principle of demand stability, attempting to reflect upon its incidence in the individual and collective civil suits. After concluding that it is about a fundamental integrant principle of the legal process, the singularities of its incidence in the collective civil suit are analyzed. We seek to demonstrate that the effectiveness principle of collective custody, that is established in the art. 83 in the Brazilian Code of Consumer Defense, requires the adoption of a processual model that is able to suit the principle of demand consistency with a certain flexibility with the collective custody. The final conclusion is that the adoption of a more flexible processual system is compatible with the singularities of the collective jurisdiction and fundamental to obtain the desired effectiveness on the collective custody